Systematic of binary phase diagrams, formed by low-melting elements (Bi, Sn, Zn, In) and the metals of IV-th and V-th periods - Vassilev G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Systematic discussion of the binary phase diagrams formed by low-melting elements (Bi, Sn, Zn, In) and the metallic elements of IV-th and V-th periods has been done. Some options for theoretical prediction of the type of the phase diagrams relying on general criteria (enthalpy of formation, assessed by the Miedema model, and size factor) have been applied, and compared with experimental data about the respective binary systems. The systematization helps to determine the scope and the limits of such an approach. These predictions have been compared with experimental data about the respective binary systems studied by the author. Forecasts for the general features of some unknown binary systems have been deduced.